UFMylation in lipid metabolism disorders-associated diseases - Zi-Ping Ning; Ya-Ling Tang; Lin Cao; Hong-Feng Gu (Molecular Biology Reports, 2026)

Integrated wet chemical process for recovery of phosphorus and metal from sewage sludge slagging gasification fly ash - Yunhui Hua; Lili Liang; Wei Ping Chan; Ya Zhao; Vernette Chin; Sofea Al Munawarah Binte Yusoff; Yinn Zhao Boon; Zahin Amrad; Yan Gu; Qinqing Cai; Miao He; Guihe Tao; et al. (Chemical Engineering Journal, 2026)

Object preference versus novelty preference: The importance of object selection and recommendations for the Novel Object Recognition test in mice - Yuan Yuan; Jing Li; Xiaoying Gu; Shuangshuang Ye; Yuanze Li; Zhuangfei Chen; Ping Ren; Yu Fu (Applied Animal Behaviour Science, 2026)

Modulating the fermented gelation behavior of pumpkin (Cucurbita moschata) seed protein isolate through ultrasound-assisted protein glutaminase deamidation - Xiaodan Zhao; Ying Wang; Youling L. Xiong; Qing Gu; Ping Li; Jiang Jiang (Food Research International, 2026)

Dual-electron reactions enabled by Se-rich interfaces in NMO@NCZ-LMS heterostructures for micro-supercapacitors - Ping Cao; Bin Cai; Hao Gu; Junlai Jiang; Jingwei Zhou; Limei Zhang; Mingzhe Shan; Heju Zhao; Hongye Chen; Ruixiang Xu (Chemical Engineering Journal, 2026)

Viable lactic acid bacteria across the production-food-gut continuum: Multi-stress adaptation and robustness engineering - Jing Cui; Jiahui Li; Meijuan Ran; Qi Chen; Jiehong Fang; Jiankang Jiang; Qing Cao; Ping Li; Han Jiang; Qing Gu (Trends in Food Science & Technology, 2026)

Metagenomic insights into microbial responses to soil amendments and oat cultivar identity in saline–alkali soils - Ping Chen; Haili Si; Juan Wang; Jingbo Xie; Chuanshen Gu; Wenli Ma; Xiaolong Liu; Quan Sun (Environmental Research, 2026)

Experimental investigation on seismic performance evolution of reinforced concrete columns considering spatially differential corrosion - Yang Liu; Wei-Ping Zhang; Qian-Qian Yu; Hao-Ran Zuo; Xiang-Lin Gu (Engineering Structures, 2026)

Monoterpenoid indole alkaloids from the aerial parts of Tabernaemontana divaricata (L.) R. Br. ex Roem. & Schult. and their anti-inflammatory activity and cytotoxicity on acute leukaemia cells - Wan-Qi Yang; Cai-Xia Wen; Er-Gu Chen; Ren-Feng Ye; Min Jiang; Gui-Guang Cheng; Ya-Ping Liu (Natural Product Research, 2026)

Study on the generation of combustion pollutants and the transformation mechanism of N during NH3/CH4 combustion under MILD conditions - Huichun Wang; Ping Chen; Yongtao Li; Mingyan Gu; Kun Luo; Xun Hu (Fuel, 2026)

Self-assembled carrier-free Cur@EGCG-Cu rescue inflammatory senescence and restore autophagy in tendinopathy - Yu Zhang; Qiqi Lou; Ran Yang; Xiang Li; Xiangkai Kong; Ruolin Cui; Ni Ni; Lilun Jin; Weiran Teng; Ping Gu (Chemical Engineering Journal, 2026)

TRPV4-mediated mechanotransduction governs surface topography-induced bone formation via macrophage-osteoclast axis - Jingqi Wu; Jiayi Gu; Ping He; Yuxiao Liu; Jingrong Chen; Lixin Yang; Wei Lei; Tong-Chuan He; Joost D. de Bruijn; Liwen Zheng; Hongmei Zhang; Huipin Yuan; et al. (Chemical Engineering Journal, 2026)

Polystyrene nanoplastics trigger ferroptosis to aggravate ulcerative colitis: Integrated multi-database bioinformatics, machine learning, and experimental validation - Meng Gu; Mengjia Tian; Chaohong Jiang; Guoqing Ping; Haixin Chen; Xuan Huang (Chemico-Biological Interactions, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Preventive Memantine Treatment at the Preclinical Stage in the Alzheimer’s Disease Model of the 5xFAD Mouse - Xiaohuan Gu; Shan Ping Yu; Michael Q. Jiang; Weiwei Zhong; Ananth Sastry; Ling Wei (Neuroscience Bulletin, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

Novel eudesmanolides from the flowers of Pentanema britannicum (L.) D.Gut.Larr with antidepressant activities - Yu-Qing Xie; Xin-Yue Zhang; Jun-Hui Zhang; Ping He; Sheng-He Yang; Yan Fu; Zhi-Yu Ni; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Ion-imprinted covalent organic framework/PVDF mixed matrix membrane: Preparation, selective removal of Cr(VI) and its adsorption behavior - Wenqiang Wang; Xinying Liu; Yuhan Lei; Zixuan Wang; Guanghui Zhang; Lihua Dong; Ping Gu; Lian Hou (Journal of Environmental Sciences, 2026)

Fatty acid composition and secondary metabolites of cypress monoculture were differently influenced by neighboring species identity - Zhengqiao Liao; Lei Liu; Yulian Yang; Nini Lu; Guilin Wu; Ping Li; Junhua Chen; Jiacun Gu; Jürgen Kreuzwieser; Christiane Werner; Baoguo Du (Forest Ecology and Management, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Efficient catalytic oxidation of toluene over a hierarchical porous Pt/ZSM-5/MCM-41 catalyst - Jinglei Cui; Ping Zhang; Yuebing Zhao; Mengyuan Gu; Jingjing Tan; Huirong Zhang; Baofeng Wang (Journal of Environmental Chemical Engineering, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Reduction mechanism of NO in high-temperature oxygen lean zone during ammonia-coal co-combustion and the influence of high humidity atmosphere - Ping Chen; Le Sun; Huichun Wang; Mingyan Gu; Kun Luo; Xun Hu (Fuel, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

A semi-supervised LSTM framework for spatiotemporal downscaling of GRACE-derived terrestrial water storage anomalies to improve flood monitoring in the Yarlung Tsangpo River basin - Ying Hu; Xiaoming Cai; Yue-Ping Xu; Haiting Gu; Jingkai Xie; Sirui Dai (Journal of Hydrology, 2026)

Proteome-wide reverse molecular docking reveals folate receptor as a mediator of PFAS-induced neurodevelopmental toxicity - Ally Xinyi Kong; Maja Johnson; Jinhua Chi; Aiden F. Eno; Khoa Pham; Ping Zhang; Haiwei Gu; Yijie Geng (Journal of Hazardous Materials, 2026)

Lactiplantibacillus plantarum ZJ316 synergizes with tryptophan diet to modulate gut microbiota and metabolite profiles in mice - Qingqing Zhou; Yingying Zhou; Lu Li; Kening Fu; Shibo Liu; Ping Li; Qing Gu (Food Bioscience, 2026)

First report of mitochondrial genomes in Hydryphantoidea: novel genomes, evolution rate, and gene rearrangement patterns in two water mites (Acari: Hydrachnidia) - Xin-Yao Gu; Ping Li; Hao Zhong; Hai-Tao Li; Jian-Jun Guo; Gang Li; Tian-Xing Jing (Experimental and Applied Acarology, 2026)

Dynamic mechanical degradation of thermally treated sandstone under impact loading: A 3D numerical analysis with experimental validation - Qiaoli Chen; Hua Lu; Xinbo Wen; Ping Wu; Zhenkun Gu (Journal of Mountain Science, 2026)

Preparation of styrene-maleic anhydride copolymer nanobrush chromatographic stationary phase and its application in phospholipid analysis of exosomes - Ping Wang; Meijuan Xue; Xinhui Guan; Xiaofei Gu; Xiaoqiang Qiao (Analytica Chimica Acta, 2026)

New sesquiterpenoids from the flowers of Pentanema britannicum with cytotoxicity activities - Jun-Hui Zhang; Ping He; Sheng-He Yang; Jia-Li Lang; Yan Fu; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

CFD-PBM-ASM2 integrated model reveals the influence mechanisms of bubble size distribution on oxygen mass transfer and pollutant removal in a full-scale A²O bioreactor - Junyan Liu; Jinze Li; Li-ping He; Li Gu (Water Research, 2026)

Mineral-associated organic carbon promotes phosphorus accumulation in a long-term fertilized black soil - Naiyu ZHANG; Xiuzhi ZHANG; Yanhua CHEN; Lehlogonolo Abner MATELELE; Ping ZHU; Hongfang LIU; Xianmei ZHANG; Hongjun GAO; Gu FENG; Chang PENG; Shuxiang ZHANG (Pedosphere, 2026)

Paleoproterozoic granite chronology, geochemical characterization, and geological significance in the Longdu region of northeastern Zambia - Yu-Xuan Wu; A-Lei Gu; Jun-Ping Ren; Ling-An Bai; Li-Bo Zuo; Hong-Wei Sun; Shi Xing; Zi-Jiang Liu (International Geology Review, 2026)

Preferences for different prey and molecular mechanisms of feeding regulation in Neptunea arthritica cumingii Crosse - Wenhui Gu; Junxia Mao; Xubo Wang; Fengxiao Lü; Ping He; Linxuan Cai; Longwei Dai; Menghao Jia; Ying Tian; Zhenlin Hao (Journal of Oceanology and Limnology, 2026)

New perspectives on key bioactive molecules of lactic acid bacteria: integrating targeted screening, key gene exploration and functional evaluation - Shi Hu; Qi Wang; Jinfeng Wu; Hangjia Zhang; Jiaqi Yin; Lina Ding; Ping Li; Hang Xiao; Qing Gu; Jiarun Han (Critical Reviews in Food Science and Nutrition, 2026)

Hydrothermal stress influences the spatial distribution pattern of soil organic carbon and its stock in Xinjiang - Yunhao Li; Mingjie Shi; Ping'an Jiang; Jinzhi Gu; Jia Guo; Jiahao Zhao; Gongxin Wang; Yanmin Fan; Hongqi Wu (CATENA, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Tumor microenvironment-driven ST6Gal-Ⅰ activation promotes aggressiveness in gastric signet-ring cell carcinoma via ITGβ1/FAK/Paxillin signaling - Shuhong Zeng; Lihuiping Tao; Yingjie Gao; Xueying Yang; Zhiyu Li; Ziwen Li; Luhua Wu; Zhengchen Ping; Qian Zhao; Jiayi Gu; Liu Li; Dongdong Sun; et al. (Tissue and Cell, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

Immune modulation of Spodoptera litura larvae parasitized by Meteorus pulchricornis and role of the host β-1, 3-glucan-binding protein in parasitism success - Yan Song; Zhi-Xiang Liu; Feng-ming Gu; Ping Li; Wei-Hong Zhou; Jun Wang; Fu-An Wu; Sheng Sheng (Pesticide Biochemistry and Physiology, 2026)

Low phosphorus promotes caryophyllene biosynthesis by regulating AaTPS3 in Artemisia argyi - ZhongWen Ma; Ping Lu; Quan Gu; ShiMin Zhang; ZhiYuan Feng; YongPing Cai; Lin Liu (Plant Cell Reports, 2026)

Enrichment and cultivation of thermophilic Bathyarchaeia from oil reservoirs via systematic cultivation profiling - Qing-Ping He; Yi-Fan Liu; Bo-Wen Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2026)

A novel GFRP lattice-foam sandwich anti-collision island: Design, experimental, numerical investigation and application - Yue Liu; Bin Liu; Ruixin Jia; Mingyang Gu; Ping Lu; Yue Wang (Engineering Structures, 2026)

Core microbiomes of Cd-hyperaccumulators are shaped by host selection and compartment identity and drive plant performance - Jipeng Luo; Yuanfan Wang; Wenzhe Gao; Yongchao Liang; He-Ping Zhao; Shaohua Gu; Tingqiang Li (Plant and Soil, 2026)

Association between low daily average temperature and epilepsy outpatient visits: a hospital-based study in Chongqing, China - Pei Jiang; Jing Yang; Yumeng Zhou; Jinchi Gu; Fengxia Liu; Chunlei Tan; Yao Cheng; Hao Wang; Li Mao; Peng Hu; Ping Chen; Ding Liu; et al. (International Journal of Biometeorology, 2026)

Lowering cyclosporine trough concentration threshold effectively mitigates acute graft-versus-host disease in children with severe β-Thalassemia post hematopoietic stem cell transplantation - Zhuolin Yang; Xianggui Wang; Xiaojing Wang; Wenjiao Ding; Yiyu Zhang; Qingling Gu; Wenqing Wang; Yousi Miao; Ping Xie; Min Huang; Hua Jiang; Xiaolan Mo; et al. (European Journal of Clinical Pharmacology, 2026)

Nutrient metabolism and microbial network complexity control soil multifunctionality in subtropical plantations under natural drought - Yuanzheng Gu; Hanjie He; Liwen Wang; Shuoxing Wei; Zhihui Wang; Hanbiao Ou; Ping Zhong; Yingping Wang; Guangjun Wang (Applied Soil Ecology, 2026)

Innovative design of CXCR4 cyclic peptide via molecular docking for 99mTc-Labeled SPECT/CT imaging in melanoma - Xianrui Yin; Xin Wang; Chengwei Chen; Shenglan Jia; Wanhong Li; Yihong Wu; Xin Chen; Danling Feng; Wai Ping Cecilia Tsang; Zhihao Han; Yueqing Gu (Analytica Chimica Acta, 2026)

Photoaging behavior and neurotoxic effects of shower gel-derived microbeads in Caenorhabditis elegans - Yulun Gu; Yajing Han; Xin Li; Ping Ding; Chaoyi Du; Xiaoxia Chen; Yongqi Jiang; Jinyu Chen; Jingwen Cui; Haibo Chen; Hui Li (Journal of Environmental Management, 2025)

Removal of Cd from severely contaminated soil by TiO2 modified magnetic sepiolite (MMSep@TiO2): The performance and possible mechanisms - Jiachao Jiang; Chunyang Gu; Yunliang Han; Xiangyu Bai; Xiaofu Shang; Jiajia Hu; Xin Xiao; Lizhang Wang; Ping Luo (Journal of Environmental Chemical Engineering, 2025)

Machine learning-assisted aroma profile prediction in tomato puree based on flavoromics - Zhihui Hu; Yufei He; Sirou Gu; Wanying He; Ping Zhan; Guangsen Fan; Honglei Tian; Hongzhi Wei; Peng Wang (Food Chemistry, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

The probiotic characteristics and antimicrobial mechanisms of Lactiplantibacillus plantarum ZFM55 - Shiying Wu; Jiayi Fan; Yi Xu; Yuenuo Luo; Luying Xie; Mingyang Hu; Yongqiang Chen; Fangtong Wei; Yuqing Lou; Ping Li; Qing Gu (Food Bioscience, 2025)

Lactiplantibacillus plantarum ZJ316 Alleviates Helicobacter pylori-Induced Intestinal Inflammation by Sustaining Intestinal Homeostasis - Shiying Wu; Fangtong Wei; Yongqiang Chen; Ziqi Chen; Yuenuo Luo; Jiayi Fan; Yang Xu; Mingyang Hu; Ping Li; Qing Gu (Probiotics and Antimicrobial Proteins, 2025)

Ionic strength modulates size-controlled ecotoxicity of citrate-coated silver nanoparticles to Daphnia magna in complex environmental matrices - Ping Luo; Zhenghao Xu; Jiageng Zhang; Xin Wang; Xiujun Gu; Lizhang Wang; Dejun Yang; Jiachao Jiang (Environmental Geochemistry and Health, 2025)

Chaotic circuit-enhanced electrokinetic leaching of ionic rare earth ores with (NH4)2SO4-MgSO4 compound salt - Yu Wan; Anqi Li; Xin Zhang; Shiliang Gu; Guocan Zheng; Qian Zhan; Jinjing Tang; Changyuan Tao; Jinhui Li; Ping Li; Zuohua Liu (Journal of Cleaner Production, 2025)

How root exudates of vegetation contribute to prevention and control of soil disintegration on Chinese Loess Plateau: A case study of Robinia pseudoacacia L. - Tao Xiao; Ping Li; Rong Jiang; Sai K. Vanapalli; Xiangcheng Han; Hui Zhai; Yiyi Yang; Qi Gu; Jiading Wang (Engineering Geology, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Development of novel smartphone-based micro-electrochemical immunosensors for the point of care testing and typing of Helicobacter pylori in serum and whole blood - Yuhan Wang; Ping Zhang; Wei Fang; Chuxian Zhou; Gengzhou Yang; Wenwei Huang; Lijie Zhang; Xiaoli Zhang; Bing Gu; Minmin Li; Jiajie Liang; Yong Tang (Chemical Engineering Journal, 2025)

Boosting simultaneous proton transfer and oxygen-related radical species generation for H2O2 photosynthesis by cationic polarization of covalent organic polymers - Danfeng Wang; Heman Xu; Feiyang Tan; Liujun Jin; Shiyuan Zhou; Xiaoqiong Hao; Shengshen Gu; Guangfeng Liu; Peng Wang; Qiuxuan Zhou; Peiyang Gu; Ping Liu (Chemical Engineering Journal, 2025)

Adsorption behavior and neurotoxic synergy of thallium and polystyrene microplastics in Caenorhabditis elegans - Chaoyi Du; Ping Ding; Hongzhi Guo; Yulun Gu; Xuefang Shi; Yuyang Ni; Shiyin Zhu; Lijuan Zhang; Haibo Chen; Jianying Qi (Aquatic Toxicology, 2025)

Rational design of hydrogel/CuPc dual-improved microelectrode for sensitive detection of bisphenol A in blood - Haifeng Zhou; Jinhong Luo; Haocheng Yang; Shengshen Gu; Ping Zou; Yalan Xu; Yingyang Zhang; Jin He (Analytica Chimica Acta, 2025)

Megastigmane glycosides from the leaves of Nicotiana tabacum and their neuroprotective activities - Jun-zhang Wu; Jun-ping Gu; Bao-min Lin; Duo-bin Mao; Hong Tao (Natural Product Research, 2025)

Supramolecular self-assembly for probiotic delivery in food system: responsive strategies, multifunctional carriers, future perspectives - Li Song; Haoting Xu; Chaofan Chen; Yubin Zhang; Zihao Zhang; Xiangfeng Chen; Shunxun Liu; Hang Xiao; Qing Gu; Ping Li (Trends in Food Science & Technology, 2025)

Extraction of lithium from cookeite-bearing claystone by chlorination roasting: From thermodynamic calculation to experimental practice - Ya Chen; Penghui Ping; Huoqiang Tang; Renlong Liang; Yongfeng Huang; Xilong Gu; Jiaqing Fan; Jiuqing Liu; Xichang Shi (Minerals Engineering, 2025)

Hydrous and oxidised deep lithospheric mantle revealed by amphibole megacrysts from the northwest North China Craton - Lin-Lin Hu; Hong-Kun Dai; Qing Xiong; Shao-Kui Pan; Jiang-Gu Lu; Jian-Ping Zheng (Lithos, 2025)

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

All-in-one wearable electronic based on bacterial cellulose composite: Integrating strain sensing and energy harvesting - Ping Sun; Zongxue Gu; Duo Xu; Bin Yu; Hui Sun; Juan Li; Nan Zhou; Jing Li; Keshuai Liu; Yingcun Liu; Chong Gao; Weilin Xu (Chemical Engineering Journal, 2025)

Permeability Correction in Low-Permeability Soils Using a Seepage Force Consolidation Test - Yao Xie; Ping-Shan Chen; Ren-Guo Gu; Jing Wang; Kang Gao; Ying-Guang Fang (Geotechnical and Geological Engineering, 2025)

Phylogenetic analysis of cyclin-dependent kinase (CDK) genes and the role of PbCDK9, PbCDK17, and PbCDK18 in cell proliferation in pear fruit - Si-Qi Zheng; Jia-Ning Kang; Pei-Zhuo Liu; Jia-Ying Ou-Yang; Tao Zhou; Zheng-Mao Zhang; Zhi-Hua Guo; Xue-Ping Wang; Shao-Ling Zhang; Chao Gu (Acta Physiologiae Plantarum, 2025)

Exogenous application of glycine betaine facilitates yam tuber healing via positively regulating suberin deposition and energy status - Guo Liu; Ping Geng; Xiaozhe Gu; Xiaoyuan Wang; Xiaopeng Wei; Jiaying Chen; Wenjie Gong; Xing Yao; Yuyao Zhou; Yalin Zhu (Postharvest Biology and Technology, 2025)

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

Investigating the Impact of Drought During Returning Green and Jointing Stages on Different Tillers Position of Winter Wheat - Muhammad Fraz Ali; Ping Li; Lijuan Ma; Changjie Feng; Shubo Gu; Xiang Lin; Dong Wang (Journal of Plant Growth Regulation, 2025)

Alkaloids from Zanthoxylum nitidum and their anti-proliferative activity against A549 cells by regulating the EGFR/AKT/mTOR pathway - Fan-Fan Wang; Ping-Fang Tao; Yu-Jun Zhong; Yun-Qiong Gu; Cai Yi Wang; Feng Qin (Natural Product Research, 2025)

High temperature slagging gasification demonstration-scale trial of sewage sludge: Feasibility analysis towards mono treatment, operational challenges and life-cycle assessment - Mei Ping Vernette Chin; Wei Ping Chan; Yinn Zhao Boon; Sofea Al Munawarah Binte Yusoff; Ya Zhao; Stephan Heberlein; Yan Gu; Qinqing Cai; Miao He; James Oh; Guihe Tao; Gurdev Singh; et al. (Waste Management, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Machine learning analysis: Environmental and operational factors' influence on decay rate and organic sludge yield in full-scale wastewater treatment plants - Jinze Li; Lizhan Tang; Junyan Liu; Li-ping He; Li Gu; Shang Cheng; Yiyuan Wei; Binquan Jiao; Yongdong Chen (Journal of Water Process Engineering, 2025)

Detection of estrous ewes’ tail-wagging behavior in group-housed environments using Temporal-Boost 3D convolution - Jinru Shi; Xinwen Chen; Yanli Zhang; Ping Gong; Yingjun Xiong; Mingxia Shen; Tomas Norton; Xingjian Gu; Mingzhou Lu (Computers and Electronics in Agriculture, 2025)

Explore the synergistic effects of Lactobacillus plantarum fermentation and tea polyphenols on the deodorization of egg white powder from the perspective of protein site competition - Ru-yi Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2025)

Amelioration of inflammation in D-galactose-induced aging C57BL/6J mice via sialoglycan-enriched soybean protein isolate - Yongjie Pan; Tiantian Zhang; Yiqun Gu; Jianrong Wu; Zhibo Hu; Ping Gong (Food Bioscience, 2025)

Study on the effect of microwave irradiation improvement on the long-term stability of expansive soil - RenLing Zhang; Qijun Hu; Yucheng Gu; Le-Ping He (Natural Hazards, 2025)

Dress me an outfit: advanced probiotics hybrid systems for intelligent IBD therapy - Yonglu Li; Yadi Wang; Yapeng Li; Shihai Yan; Xin Gao; Ping Li; Xiaodong Zheng; Qing Gu (Critical Reviews in Food Science and Nutrition, 2025)

Understanding citrus aroma: Changes induced by postharvest treatments of fresh fruit - Shuxun Liu; Yuling Cai; Ying Lou; Yan Zhao; Mingfeng Cao; Ping Li; Qing Gu (Postharvest Biology and Technology, 2025)

In vitro and in vivo antibacterial effects of indole-3-lactic acid against Salmonella enterica serovar Typhimurium - Qingqing Zhou; Yajun Yu; Zuorui Xie; Yingying Zhou; Yanan Li; Ping Li; Jiangning Hu; Qing Gu (Food Bioscience, 2025)

Four new pregnane C21 steroids isolated from the roots of Cynanchum auriculatum - Yi-min Fan; Ping Yi; Jun Jin; Jun-you Jian; Wei Gu; Chun-mao Yuan; Zhan-xing Hu; Xiao-jiang Hao; Lie-jun Huang (Natural Product Research, 2025)

Multistage hydrothermal fluids evolution and precipitation mechanism of the Hongshi Cu deposit in Eastern Tianshan, NW China: Insights from cathodoluminescence, fluid inclusions, trace elements of quartz and in situ S isotopes of sulfides - Wen-Xin Gu; Yin-Hong Wang; Jian-Ping Wang; Kang Wang; Wei Zhang; Hui Zhang (Journal of Geochemical Exploration, 2025)

Effect of γ-Aminobutyric acid and dietary monosodium glutamate supplementation on gut microbiota and short-chain fatty acid: Insights from an in vitro colonic fermentation model - Jiarun Han; Xilian Zhao; Qiuqiu Ye; Yueting Wang; Yutong Wu; Shi Hu; Ping Li; Qing Gu (Food Bioscience, 2025)

Regulatory effects of Lacticaseibacillus rhamnosus ZFM216 and its bacteriocin on intestinal microbiota in vitro - Qingqing Zhou; Yeqing Lou; Chenjie Shan; Zhongdu Ye; Danli Wu; Ping Li; Eefjan Breukink; Qing Gu (Food Bioscience, 2025)

Study on the adsorption mechanism of NO/C3H6O on the surface of metallic calcium coupled nitrogen-doped biochar - Yue Zhao; Ping Chen; Huichun Wang; Mingyan Gu; Kun Luo (Biomass and Bioenergy, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

miRNA-125a regulates porcine oocyte maturation in vitro by targeting ADAR - Yue Han; Ping Lu; Yongsheng Yu; Weiyu Gu; Chunyu Li; Yanqiu Lv; Xinglin Qu; Yuyang Zhang; Qinglong Xu; Shunfa Yao; Xuan Chen; Yi Jin (Theriogenology, 2025)

Pantoea jilinensis D25 promotes tomato growth and induces resistance to tomato gray mold (causative agent Botrytis cinerea) - Lining Zheng; Xuehu Gu; Ping Chen; Hongyu Pan; Hao Zhang; Jingyuan Chen (Physiological and Molecular Plant Pathology, 2025)

Defective Zn1-xCuxS nanosheet as efficient and durable cathode catalyst for photo-assisted Li-O2 batteries - Cong-Cong Dang; Yi-Ping Liu; Yu-Xin Huang; Xin-Yi Zhang; Zhen-Yi Gu; Jun-Ming Cao; Jin-Zhi Guo; Li-Ming Gao; Xing-Long Wu; Yi-Chun Liu (Chemical Engineering Journal, 2025)

Corrigendum to “Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment” [Chem. Eng. J. 479 (2024) 147436] - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2025)

Multifunctional flexible MXene/TA@CNC electronic hydrogel patch with robust adhesion and self-healing properties for wearable electronics - Haoyu Wang; Ping Han; Ying Yu; Shaolong Han; Yue Qiao; Yuehan Li; Bin Sun; Zheng Gu (Chemical Engineering Journal, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Enhanced spatiotemporal fusion algorithm for long-term monitoring of intertidal zone topography - Jianchun Chen; Yan Gu; Ziyao Chen; Shibing Zhu; Ya Ping Wang (Geo-Marine Letters, 2025)

Natural acidic deep eutectic solvent-mediated microwave-assisted simultaneous hydrodistillation, hydrolysis, and extraction for obtaining essential oils, gallic acid and ellagic acid from Liquidambar formosana leaves and fruits - Ke Zhang; Hongfei Gao; Yang Yang; Yifan Ping; Hao Tian; Huiyan Gu; Lei Yang (Sustainable Chemistry and Pharmacy, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Unveiling the mechanism of Latilactobacillus sakei LZ217 cell-free supernatant against Helicobacter pylori through metabolomics and network pharmacology - Chenlan Xia; Qingqing Zhou; Xia Meng; Ziqi Chen; Shiying Wu; Ping Li; Qing Gu (Food Bioscience, 2025)

Lactate-triggered histone lactylation contributes to podocyte epithelial-mesenchymal transition in diabetic nephropathy in mice - Ting Zheng; Yan-Ping Gu; Jiang-Meng Wang; Ting-Ting Huang; Ling-Shan Gou; Yao-Wu Liu (Chemico-Biological Interactions, 2025)

Optimization of Melliodendron xylocarpum multiplication medium formulation using response surface methodology - Yiting Gu; Chen Wang; Yifan Leng; Ping Gao; Min Li; Shusheng Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Technical and environmental assessment of sludge-derived slag generated from high temperature slagging co-gasification process as a sustainable construction material - Ya Zhao; Wei Ping Chan; Vernette Chin; Yinn Zhao Boon; Xiaoxu Fu; Yan Gu; James Oh; Grzegorz Lisak (Waste Management, 2024)

Sediment dynamic responses of coastal salt marsh to wind waves and swells in a semi-open tidal flat - Shaoxin Chen; Weifang Gu; Benwei Shi; Yining Chen; Antonis Chatzipavlis; Jiawei Ding; Wenxiang Zhang; Qi Chen; Ya Ping Wang (Science of The Total Environment, 2024)

Multi-omics analyses of the mechanism for formation of key aroma-active compounds in blood orange wine fermented by Pichia kudriavzevii - Shuxun Liu; Ying Lou; Yan Zhao; Yuling Cai; Mingfeng Cao; Yixian Li; Ping Li; Qing Gu (Food Research International, 2024)

Corrigendum to “An isolated salt-tolerant Tetragenococcus halophilus 2MH-3 improved the volatile flavor of low-salt fermented fish sauce by regulating the microbial community” [Food Res. Int. 196 (2024) 115052] - Jiarun Han; Shi Hu; Xin Zhao; Jialan Jiang; Qi Wang; Jinfeng Wu; Xilian Zhao; Ping Li; Qing Gu (Food Research International, 2024)

Natural surfactant used as an additive in the enzymatic-homogenate synergistic extraction of piceatannol, resveratrol, and myricetin from the myrtle (Rhodomyrtus tomentosa) fruit - Yifan Ping; Yang Yang; Hongfei Gao; Xiuwei Liu; Jun Pan; Ke Zhang; Huiyan Gu; Hao Tian; Lei Yang (Food Bioscience, 2024)

Molecular evidence of internal carbon-driven partial denitrification in a mainstream pilot A-B system coupled with side-stream EBPR treating municipal wastewater - Da Kang; Yuan Yan; IL Han; Jangho Lee; Kester McCullough; Guangyu Li; Zijian Leo Wang; Peisheng He; Dongqi Wang; Stephanie Klaus; Ping Zheng; Varun Srinivasan; et al. (Water Research, 2024)

Association between PFAS exposure and thyroid health: A systematic review and meta-analysis for adolescents, pregnant women, adults and toxicological evidence - Xiushuai Du; Yitian Wu; Gonghua Tao; Jun Xu; Zhiyuan Du; Minjuan Wu; Tianmin Gu; Jiasheng Xiong; Shuo Xiao; Xiao Wei; Yuanyuan Ruan; Ping Xiao; et al. (Science of The Total Environment, 2024)

Pyrite functionalized Black Soldier Fly feces biochar for mine soil quality improvement and heavy metals immobilization - Chuang Li; Lei Zhao; Ping Chen; Shujing Ye; Hailan Yang; Yanling Gu; Shaobo Liu; Zhiming Yang; Xinjiang Hu; Xiaofei Tan (Process Safety and Environmental Protection, 2024)

Enhanced rainfall nowcasting of tropical cyclone by an interpretable deep learning model and its application in real-time flood forecasting - Li Liu; Xiao Liang; Yue-Ping Xu; Yuxue Guo; Quan J. Wang; Haiting Gu (Journal of Hydrology, 2024)

Cu/Fe3O4 magnetic aerogel for the capture and immobilization of iodine anion from water - Xin-Yu Zhou; Kai-Wei Chen; Ao-Tian Gu; Hui-Ran Jin; Wei-Jie Sun; Shu-Chao Song; Shan Yun; Ping Mao; Yi Yang; Jing Chen (Journal of Cleaner Production, 2024)

An isolated salt-tolerant Tetragenococcus halophilus 2MH-3 improved the volatile flavor of low-salt fermented fish sauce by regulating the microbial community - Jiarun Han; Shi Hu; Xin Zhao; Jialan Jiang; Qi Wang; Jinfeng Wu; Xilian Zhao; Ping Li; Qing Gu (Food Research International, 2024)

Tunable sulfur vacancies in amorphous-crystalline AC-Bi2S3-x@C derived from CAU-17 for efficient capture of radioiodine: Comparison of sulfur vacancies in amorphous and crystalline structures - Kai-Wei Chen; Xin-Yu Zhou; Yi-Ting Chen; Xiao-Jun Dai; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ping Mao; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2024)

Increasing parameter identifiability through clustered time-varying sensitivity analysis - Lu Wang; Yue-Ping Xu; Jiliang Xu; Haiting Gu; Zhixu Bai; Peng Zhou; Hongjie Yu; Yuxue Guo (Environmental Modelling & Software, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Rich-silicon rice husk ash increases iron plaque formation and decreases cadmium and arsenic accumulation in rice seedlings - Jiao-Feng Gu; Xuan-Tao Yi; Kun Ouyang; Qian Li; Ping You; Rui Zhou; Peng Zeng; Ye Liao; Hang Zhou (Chemosphere, 2024)

Segmentation of wood CT images for internal defects detection based on CNN: A comparative study - Guangqiang Xie; Lihai Wang; Roger A. Williams; Yaoxiang Li; Ping Zhang; Sheng Gu (Computers and Electronics in Agriculture, 2024)

A novel bacteriocin against methicillin-resistant Staphylococcus aureus, purified from Lactiplantibacillus plantarum ZFM9 - Zhongdu Ye; Huifei Shentu; Qingqing Zhou; Danli Wu; Ping Li; Qing Gu (Food Chemistry, 2024)

Microplastic pollution characteristics and ecological risk assessment in the Wuding River Basin, China - Shun Wan; Guoce Xu; Ping Xiong; Hailiang Qiao; Xin Chen; Liuyang Gu; Haijing Xiong; Bin Wang; Fengyou Gu (Environmental Pollution, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

Discovery and Exploration of Lipid-Modifying Drug Targets for ALS by Mendelian Randomization - Zheng Jiang; Xiao-Jing Gu; Wei-Ming Su; Qing-Qing Duan; Kang-Fu Yin; Yan-Lin Ren; Yi Wang; Bei Cao; Yong-Ping Chen (Molecular Neurobiology, 2024)

Electrical structure identification of deep shale gas reservoir in complex structural area using wide field electromagnetic method - Zhi-Wen Gu; Yue-Gang Li; Chang-Heng Yu; Zhong-Ping Zou; Ai-Guo Hu; Xue-Bo Yin; Qinag Wang; Heng Ye; Zhang-Kun Tan (Applied Geophysics, 2024)

New cassane diterpenoids from the seeds of Pterolobium macropterum - Yue-ping Lan; Wen-jian Gu; Ming Yang; Pu-Zhao Zhang (Phytochemistry Letters, 2024)

Negative rejection phenomenon in the mixed salt nanofiltration: Law and mechanism - Gao Xuerui; Li Ping; Qin Yuan; Bai Chengling; Gu Zhengyang; Yu Shuili (Desalination, 2024)

Efficacy and safety of dabigatran and rivaroxaban in atrial fibrillation patients with impaired liver function: a multicenter retrospective cohort study - Xinhai Huang; Wenlin Xu; Guilan Wu; Ruijuan Li; Ping Gu; Qiaowei Zheng; Xiumei Liu; Hengfen Dai; Xiangsheng Lin; Yuxin Liu; Xiaoming Du; Jun Su; et al. (European Journal of Clinical Pharmacology, 2024)

Hydrolysis reactivity reveals significant seasonal variation in the composition of organic peroxides in ambient PM2.5 - Yishuang Dai; Zhongming Chen; Xuan Qin; Ping Dong; Jiayun Xu; Jingcheng Hu; Linghao Gu; Shiyi Chen (Science of The Total Environment, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Kidney-targeted antioxidant salvianolic acid B nanoparticles restoring lysosome homeostasis for acute kidney injury therapy - Jian-Li Chen; Xiao-Hui Jia; Xuan Wu; Ming-Heng Yuan; Xinyue Xia; Dan Yin; Xu Chen; Ze-Yun Gu; Jia-Zheng Liu; Li-Ping Bai; Kathy Qian Luo; Jianfang Wang; et al. (Chemical Engineering Journal, 2024)

High-precision microcline 40Ar/39Ar dating by combined techniques - Xiu-Juan Bai; Yi-Long Li; Rong-Guo Hu; Xiao Liu; Bin Tang; Xiang-Ping Gu; Hua-Ning Qiu (Chemical Geology, 2024)

Research and application progress of microbial β-mannanases: a mini-review - Ping Wang; Xiaohui Pei; Weiqiang Zhou; Yue Zhao; Pengfei Gu; Yumei Li; Juan Gao (World Journal of Microbiology and Biotechnology, 2024)

Genetic differences among populations of Gynura procumbens (Lour.) Merr - Jiangfan Yu; Xinjian Tan; Dunyuan Huang; Qiuping Zhong; Ping Gu; Youcheng Zhou; Linqing Cao; Liyun Wang; Xirui Wan; Chuansong Chen; Yaqi Yuan; Hongyan Guo; et al. (Genetic Resources and Crop Evolution, 2024)

Research progress on improving the freeze-drying resistance of probiotics: A review - Sitong Ge; Jiarun Han; Qiaoyu Sun; Qingqing Zhou; Zhongdu Ye; Ping Li; Qing Gu (Trends in Food Science & Technology, 2024)

Antimony and arsenic migration in a heterogeneous subsurface at an abandoned antimony smelter under rainfall - Chao Li; Yiyuan Ran; Pan Wu; Peng Liu; Boyi Yang; Xueyuan Gu; Ping Zhao; Shirong Liu; Lei Song; Yuhui Liu; Yizhang Liu; Zengping Ning; et al. (Journal of Hazardous Materials, 2024)

Analysis of factors influencing the energy efficiency in Chinese wastewater treatment plants through machine learning and SHapley Additive exPlanations - Jinze Li; Zexuan Du; Junyan Liu; Linji Xu; Li-ping He; Li Gu; Hong Cheng; Qiang He (Science of The Total Environment, 2024)

Effect of ammonia on N migration and transformation characteristics during coal pyrolysis: Quantum chemical calculations and pyrolysis experiments - Ping Chen; Longxiang Qiao; Cheng Gong; Mingyan Gu; Kun Luo; Jianren Fan (Fuel, 2024)

Effects of metal-coupled exogenous nitrogen on the performance of supercapacitors based on biomass carbon materials - Shuai Zou; Lu Zeng; Ping Chen; Mingyan Gu; Kun Luo; Jianren Fan; Yi Wang (Biomass and Bioenergy, 2024)

Multiple organs injury and myocardial energy metabolism disorders induced by isoproterenol - Xiao-ting Zhang; Xu Zhang; Meng-wei Wang; Chen Zhang; Rui Weng; Xu Xu; Zu-xi Gu; Jian-ping Gao (Toxicology, 2024)

Dynamics of benthic microeukaryotic communities in a mangrove wetland invaded by Spartina alterniflora: Effects of vegetation, seasonality, and sediment depth - Ying Wang; Jie Kong; Songsong Gu; Bangqin Huang; Ping Sun (Science of The Total Environment, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Experimental and mechanism study on NO formation characteristics and N chemical reaction mechanism in ammonia-coal co-firing - Ping Chen; Cheng Gong; Changhao Hua; Peipei Wang; Mingyan Gu; Kun Luo; Jianren Fan; Yi Wang (Fuel, 2024)

Photoaging enhances combined toxicity of microplastics and tetrabromobisphenol A by inducing intestinal damage and oxidative stress in Caenorhabditis elegans - Haibo Chen; Xiaoxia Chen; Ping Ding; Yulun Gu; Yongqi Jiang; Xintong Li; Guocheng Hu; Liangzhong Li; Chen Wang; Jun Yu; Hui Li (Science of The Total Environment, 2024)

Degradation mechanism of antibiotics by flower-like Bi2S3 sensitized anatase/rutile TiO2 coupled with SiO2 photonic crystals - Ruizhen Liu; Huaiyuan Jiang; Ping Li; Jianfei Yin; Zhengrui Xu; Xiaoyu Chen; Jian Cheng; Shuangxi Gu; Renliang Lyu (Journal of Water Process Engineering, 2024)

Selecting autochthonous lactic acid bacteria for co-inoculation in Chinese bayberry wine production: Stress response, starter cultures application and volatilomic study - Qing Gu; Yixian Li; Ying Lou; Yan Zhao; Xujie Feng; Ping Li; Oskar Laaksonen; Baoru Yang; Vittorio Capozzi; Shuxun Liu (Food Research International, 2024)

Comparative analysis of key precursors and metabolites involved in flavor formation of different rapid-fermented Chinese fish sauces based on untargeted metabolomics analysis - Jiarun Han; Jialan Jiang; Xin Zhao; Xilian Zhao; Tao Kong; Ping Li; Qing Gu (Food Chemistry, 2024)

Layered double hydroxide@zeolite composite modified sponge: A versatile biocarrier for enhancing nitrogen removal in biofilters - Zhuwu Jiang; Mengfan Wu; Panyang Gu; Wenzhong Huang; Chang-Ping Yu; Zhongjian Zheng; Yanqu Wang; Ning Yao; Yan Li (Chemical Engineering Journal, 2024)

Composition and concentration of suspended matter in the Zhongsha Great Atoll, South China Sea, before and during the summer monsoon - Wenwen Yan; Jun Du; Dongqi Gu; Yongzhi Wang; Guoqiang Xu; Guanxun Wang; Yonggen Sun; Ping Li; Wei Chen (Frontiers in Marine Science, 2024)
Suspended matter in seawater carries abundant nutrients and carbon, playing a significant role in carbon cycle and ecosystem in many oceanic settings such as atolls. The Zhongsha Great Atoll (hereafter ZGA), located in the deep South China Sea, sustains a both regionally and globally important ecosystem. Characteristic of the suspended matter in this area, however, remains poorly investigated. Using a data set encompassing temperature, salinity, depth, and suspended matter concentration (hereafter SMC) of seawater collected respectively in May 2019 (spring-summer monsoon transition period) and June 2020 (summer monsoon outbreak period) in the ZGA, the main components and spatial distribution of suspended matter together with their influencing factors were comprehensively analyzed. Our results show that the components of suspended matter vary widely in space and include more than 20 types of materials such as planktonic remains and biogenic siliceous debris. During the transit between spring and summer monsoons, the SMC in seawater was generally low, with an average value of approximately 3.26 mg L -1 , which decreased from the surface to the middle layer and then increased to deep waters; Horizontally, the SMC in the west was generally higher than that in the east likely because the wind-driven current transport significant amounts of particles from the east to the west. During the 2020 summer monsoon outbreak, average SMC in this area was 6.27 mg L -1 , higher than that during the 2019 spring-summer monsoon transit. Moreover, significantly higher SMC in the 1-100 m layer and lower SMC in the 150 m layer were observed in the west. Owing to the impact of mesoscale eddies, low SMC in the surface layer and high concentrations in the bottom layer can occur in parts of the ZGA, leading to the deepening of the west-high and east-low distribution layers of SMC during the 2020 summer monsoon outbreak. Notably, we for the first time have observed an anomalously high SMC in the 1–100 m layer of the northwest area during the 2020 summer monsoon outbreak. This anomaly is higher than any previously reported values in the South China Sea and can be attributed to the multiple monsoon impacts. Sources of suspended matter, topography, currents, and wind field were identified as the main factors influencing the spatial distribution of SMC in this area. Our findings provide a basic context for understanding the sources and dynamics of suspended material in atolls.

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Different long-term fertilization regimes affect soil protists and their top-down control on bacterial and fungal communities in Mollisols - Xiaojing Hu; Haidong Gu; Junjie Liu; Dan Wei; Ping Zhu; Xi'an Cui; Baoku Zhou; Xueli Chen; Jian Jin; Guanghua Wang (Science of The Total Environment, 2024)

Environmentally persistent free radicals on photoaged nanopolystyrene induce neurotoxicity by affecting dopamine, glutamate, serotonin and GABA in Caenorhabditis elegans - Hui Li; Yulun Gu; Yongqi Jiang; Ping Ding; Xiaoxia Chen; Chao Chen; Ruolin Pan; Chongli Shi; Susu Wang; Haibo Chen (Science of The Total Environment, 2024)

Flexible catabolism of monoaromatic hydrocarbons by anaerobic microbiota adapting to oxygen exposure - Zhiming Wu; Xin Yu; Yanhan Ji; Guiping Liu; Ping Gao; Lei Xia; Pengfa Li; Bin Liang; Shiri Freilich; Lifeng Gu; Wenjing Qiao; Jiandong Jiang (Journal of Hazardous Materials, 2024)

Influence of migrants’ health status on their perceived acceptance in receiving cities: Moderating role of hukou thresholds and environmental amenities - Zhihao Zhao; Hengyu Gu; Ping Lei; Fenghua Wen (Journal of Cleaner Production, 2024)

Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2024)

Iron overload induces colitis by modulating ferroptosis and interfering gut microbiota in mice - Ke Gu; Aimin Wu; Bing Yu; Tingting Zhang; Xin Lai; Junzhou Chen; Hui Yan; Ping Zheng; Yuheng Luo; Junqiu Luo; Junning Pu; Quyuan Wang; et al. (Science of The Total Environment, 2023)

Comparison of anthocyanin and volatile organic compounds in juices and fruit wines made from blood oranges (Citrus sinensis L. Osbeck) at different maturity stages - Shuxun Liu; Ying Lou; Yixian Li; Yan Zhao; Xujie Feng; Vittorio Capozzi; Oskar Laaksonen; Baoru Yang; Ping Li; Qing Gu (Food Bioscience, 2023)

Ti3C2Tx quantum dot-modified Ti3C2Tx nanosheets freestanding films for flexible solid-state pseudocapacitors - Ping Liu; Handan Liu; Tengfei Zhang; Long Chen; Wen Guo; Tiantian Gu; Feng Yu; Yanyan Liu; Gang Wang (Chemical Engineering Journal, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Dry and wet seasonal variations of the sediment fungal community composition in the semi-arid region of the Dali River, Northwest China - Xin Chen; Guoce Xu; Ping Xiong; Jianbo Peng; Kang Fang; Shun Wan; Bin Wang; Fengyou Gu; Jing Li; Haijing Xiong (Environmental Science and Pollution Research, 2023)

Studying the mechanism and impact of H2O-rich atmosphere on N oxidation during ammonia combustion and ammonia-coal co-combustion - Ping Chen; Boyu Jiang; Mingyan Gu; Kun Luo; Jianren Fan; Yi Wang (Fuel, 2023)

Optimizing root system architecture to improve root anchorage strength and nitrogen absorption capacity under high plant density in maize - Ping Zhang; Yuanyuan Wang; Dechang Sheng; Shuai Zhang; Shuangcheng Gu; Ye Yan; Fucheng Zhao; Pu Wang; Shoubing Huang (Field Crops Research, 2023)

Corrosion-induced moment redistributions of RC frame structures under service loads - Chao Jiang; Deng-Feng Shang; Xiang-Lin Gu; Hong-Fei Zhang; Wei-Ping Zhang (Engineering Structures, 2023)

Regulation of microbial metabolism on the formation of characteristic flavor and quality formation in the traditional fish sauce during fermentation: a review - Jiarun Han; Tao Kong; Qi Wang; Jialan Jiang; Qingqing Zhou; Ping Li; Beiwei Zhu; Qing Gu (Critical Reviews in Food Science and Nutrition, 2023)

Study on the influence mechanism of mineral Ca on NO reduction in the high temperature oxygen-lean zone of ammonia-coal co-combustion - Xiangyong Huang; Ping Chen; Ying Wang; Mingyan Gu; Yao Fang; Jianren Fan; Yi Wang (Fuel, 2023)

Aroma characteristics of volatile compounds brought by variations in microbes in winemaking - Shuxun Liu; Ying Lou; Yixian Li; Yan Zhao; Oskar Laaksonen; Ping Li; Jiaojiao Zhang; Maurizio Battino; Baoru Yang; Qing Gu (Food Chemistry, 2023)

Microbial colonization of microplastics in wastewater accelerates the aging process associated with oxidative stress and the insulin/IGF1 signaling pathway - Haibo Chen; Mengfan Chen; Yulun Gu; Yongqi Jiang; Ping Ding; Chen Wang; Ruolin Pan; Chongli Shi; Hui Li (Environmental Pollution, 2023)

Orally Induced High Serum Level of Trimethylamine N-oxide Worsened Glial Reaction and Neuroinflammation on MPTP-Induced Acute Parkinson’s Disease Model Mice - Chen-Meng Qiao; Wei Quan; Yu Zhou; Gu-Yu Niu; Hui Hong; Jian Wu; Li-Ping Zhao; Ting Li; Chun Cui; Wei-Jiang Zhao; Yan-Qin Shen (Molecular Neurobiology, 2023)

Comparative analysis of volatile compounds and microbial community succession in Chinese fish sauce: Three typical types of fast-fermented fish sauces - Jiarun Han; Jialan Jiang; Tao Kong; Xilian Zhao; Xin Zhao; Ping Li; Qing Gu (Food Bioscience, 2023)

The innovative and accurate detection of heavy metals in foods: A critical review on electrochemical sensors - Ruonan Meng; Qiujin Zhu; Tingyu Long; Xuli He; Zewei Luo; Ronghui Gu; Wenzhong Wang; Ping Xiang (Food Control, 2023)

Time-dependent reliability analysis of reinforced concrete beams considering marine environmental actions - Hong-Yuan Guo; Chao Jiang; Xiang-Lin Gu; You Dong; Wei-Ping Zhang (Engineering Structures, 2023)

Predicting Ecological Distribution of the Toxic Dinoflagellate Alexandrium minutum in China Sea Using Ecological Niche Modeling - Changyou Wang; Ping Zheng; Haifeng Gu; Zhaohe Luo; Zhuhua Luo; Longjiang Mao; Yuanzhi Zhang (Journal of Ocean University of China, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

Heavy metal(loid)s in agriculture soils, rice, and wheat across China: Status assessment and spatiotemporal analysis - Cheng-Chen Wang; Qiao-Chu Zhang; Chang-An Yan; Guo-Yong Tang; Meng-Yan Zhang; Lena Q. Ma; Rong-Hui Gu; Ping Xiang (Science of The Total Environment, 2023)

Calibration analysis of calculation formulas for shear capacities of corroded RC beams - Chao Jiang; Hao Ding; Xiang-Lin Gu; Wei-Ping Zhang (Engineering Structures, 2023)

Converting sludge to slag through a high temperature slagging co-gasification process: An evaluation based on a demonstration trial and life cycle assessment - Xiaoxu Fu; Wei Ping Chan; Vernette Chin; Yinn Zhao Boon; Wenqian Chen; Ya Zhao; Stephan Heberlein; Yan Gu; James Oh; Grzegorz Lisak (Chemical Engineering Journal, 2023)

Trimetallic MOFs-derived Fe-Co-Cu oxycarbide toward peroxymonosulfate activation for efficient trichlorophenol degradation via high-valent metal-oxo species - Aotian Gu; Kaiwei Chen; Xinyu Zhou; Chunhui Gong; Peng Wang; Yan Jiao; Ping Mao; Kai Chen; Jigen Lu; Yi Yang (Chemical Engineering Journal, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Mechanism analysis of fuel-N oxidation during ammonia-coal co-combustion: Influence of H2O - Ping Chen; Cheng Gong; Changhao Hua; Mingyan Gu; Boyu Jiang; Jianren Fan; Yi Wang (Fuel, 2023)

Conductive materials enhance microbial salt-tolerance in anaerobic digestion of food waste: Microbial response and metagenomics analysis - Jianhao Li; Xiaofeng Xu; Cong Chen; Linji Xu; Zexuan Du; Li Gu; Ping Xiang; Dezhi Shi; Xiaoliu Huangfu; Feng Liu (Environmental Research, 2023)

Failure mode-based calculation method for bearing capacities of corroded RC columns under eccentric compression - Chao Jiang; Hao Ding; Xiang-Lin Gu; Wei-Ping Zhang (Engineering Structures, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

miR-124-3p regulates the proliferation and differentiation of retinal progenitor cells through SEPT10 - Bingqiao Shen; Huiqin Gao; Dandan Zhang; Huan Yu; Junjue Chen; Shouyue Huang; Ping Gu; Yisheng Zhong (Cell and Tissue Research, 2023)

Metagenomic strategies uncover the soil bioavailable phosphorus improved by organic fertilization in Mollisols - Xiaojing Hu; Haidong Gu; Junjie Liu; Dan Wei; Ping Zhu; Xi’an Cui; Baoku Zhou; Xueli Chen; Jian Jin; Xiaobing Liu; Guanghua Wang (Agriculture, Ecosystems & Environment, 2023)

Multi-objective robust optimization of reservoir operation for real-time flood control under forecasting uncertainty - Xinting Yu; Yue-Ping Xu; Haiting Gu; Yuxue Guo (Journal of Hydrology, 2023)

Modeling electrochemical chloride extraction process in cement-based materials considering coupled multi-ion transports and thermodynamic equilibriums - Chao Jiang; Chen Song; Xiang-Lin Gu; Qiang Zhang; Wei-Ping Zhang (Journal of Cleaner Production, 2023)

An overlooked influence of reactive oxygen species on ammonia-oxidizing microbial communities in redox-fluctuating aquifers - Helin Wang; Ping Li; Xiaohan Liu; Jing Zhang; Lisa Y. Stein; Ji-Dong Gu (Water Research, 2023)

Authigenic beryllium isotopes reveal fluctuations in the East Asian monsoon over the past two millennia - Zhen-Ping Cao; Ye Yang; Sheng Xu; Hai Xu; Zhaoyan Gu; Guoqiang Chu (Quaternary Science Reviews, 2023)

Effects of hydroxylation at C3′ on the B ring and diglycosylation at C3 on the C ring on flavonols inhibition of α-glucosidase activity - Yajuan Qin; Xiaoai Chen; Fei Xu; Chunhe Gu; Kexue Zhu; Yanjun Zhang; Gang Wu; Ping Wang; Lehe Tan (Food Chemistry, 2023)

Tailorable carbon cloth electrodes covered with heterostructured Co/CoO/CoN interfaces for scalable electrocatalytic overall water splitting - Wei Zhang; Cong Li; Jun-Yang Ji; Zheng Niu; Hongwei Gu; Brendan F. Abrahams; Jian-Ping Lang (Chemical Engineering Journal, 2023)

Effects of Reticuloendotheliosis virus on TLR-3/IFN-Β pathway in specific pathogen-free chickens - Wen-Jie Wu; Xiao-Ping Lv; Xiao-Yan Wang; Xue-Li Gao; Chao-Nan Liu; Chen-Hui Zhao; Xian-Zhe Gu; Shi-Min Zheng (Research in Veterinary Science, 2023)

Influence mechanism of ammonia mixing on NO formation characteristics of pulverized coal combustion and N oxidation in ammonia-N/coal-N - Ping Chen; Changhao Hua; Boyu Jiang; Mingyan Gu; Zhenling Ge; Meng Zhang; Kun Luo; Jianren Fan; Yi Wang (Fuel, 2023)

Using transcriptomics, proteomics and phosphoproteomics as new approach methodology (NAM) to define biological responses for chemical safety assessment - Yuan Li; Zhenpeng Zhang; Songhao Jiang; Feng Xu; Liz Tulum; Kaixuan Li; Shu Liu; Suzhen Li; Lei Chang; Mark Liddell; Fengjuan Tu; Xuelan Gu; et al. (Chemosphere, 2023)

Effect of Tribute citrus essential oil nanoemulsion-loaded gelatin on the gel behavior and gelation surface morphologies - Guoqiang Li; Qingqing Zhou; Shuxun Liu; Cheng Qian; Jiarun Han; Tao Zhou; Ping Li; Qing Gu (Food Bioscience, 2023)

Caenorhabditis elegans: a nature present for advanced food science - Yonglu Li; Yadi Wang; Ping Li; Qingqing Zhou; Xiaodong Zheng; Qing Gu (Current Opinion in Food Science, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Investigation of the relationship between MBP gene polymorphisms and delayed encephalopathy after acute carbon monoxide poisoning - Fan Zhang; Jiao Zeng; Xiaoli Zhang; Jiapeng Gu; Yongkai Han; Ping Zhang; Wenqiang Li; Renjun Gu (NeuroToxicology, 2023)

Development, characterisation, and in vitro anti-tumor effect of self-microemulsifying drug delivery system containing polyphyllin I - Xin Wang; Rui Zhang; Shu Wang; Minju Gu; Yuan Li; Xiuping Zhuang; Chao Chen; Peimin Yang; Gongling Guo; Ping Sun (Drug Delivery and Translational Research, 2023)

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease - Cheng-Jie Li; Li-Ge Zhang; Lu-Bing Liu; Meng-Qi An; Li-guo Dong; Han-Ying Gu; Yong-Ping Dai; Fen Wang; Cheng-Jie Mao; Chun-Feng Liu (Molecular Neurobiology, 2022)

Experimental Study on Pyrolysis of Rice Straw Catalyzed by CaO/Al2O3-Phosphate Mixture - Lianlian Xu; Zhongwen Xu; Feng Zhang; Yinmei Yuan; Bin Cheng; Chuang Zhang; Ping Chen; Xiangyong Huang; Yuyu Lin; Mingyan Gu (BioEnergy Research, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

Genome-Wide Bisulphite Sequencing Uncovered the Contribution of DNA Methylation to Rice Short-Term Drought Memory Formation - Shuyan Kou; Qiongyao Gu; Liu Duan; Gaojing Liu; Pingrong Yuan; Huahui Li; Zhigang Wu; Weihua Liu; Ping Huang; Li Liu (Journal of Plant Growth Regulation, 2022)
Rice is the important crop for more than half of the world population. However, drought can have a devastating impact on rice growth and reduce yield drastically. Understanding the response of rice to drought stress is especially important for crop breeding. Previously we found that rice enhanced its tolerance to drought stresses via stress memory mechanisms. Numerous memory genes were identified to play important roles in the process. DNA methylation was reported to mediate tolerance via regulating gene expression and enhances the survival rate of rice encountering drought stress. However, how DNA methylation involved in stress memory is still not clear. In this study, genome-wide bisulphite sequencing at a single base resolution methylome profiling level was performed and analyzed in rice cultivar under recurrent drought stresses and recovery treatments. We found that rice drought stress memory-related differentially methylated regions (DMRs) showed dynamic and distinct patterns. The drought-memory DMRs may regulate Transposable elements and gene expression to cope with short-term repeated drought stresses. Our findings of drought-memory DMRs can explain mechanisms of rice drought stress memory in a new perspective on global methylome details. Using epigenetic markers to breed drought-resistant rice would become a feasible way in the future research.

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

TREM2 and CD163 Ameliorate Microglia-Mediated Inflammatory Environment in the Aging Brain - Xue Han; Yu-Jia Liu; Bin-Wen Liu; Zheng-Liang Ma; Tian-Jiao Xia; Xiao-Ping Gu (Journal of Molecular Neuroscience, 2022)

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

New sesquiterpeniod esters form Blumea balsamifera (L.) DC. and their anti-influenza virus activity - Yan Xiong; Ping Yi; Yuhuan Li; Rongmei Gao; Junlei Chen; Zhanxing Hu; Huayong Lou; Caixia Du; Jiayu Zhang; Yu Zhang; Chunmao Yuan; Liejun Huang; et al. (Natural Product Research, 2022)

Correction to: Proteasome-dependent inactivation of Akt is essential for 12-O-tetradecanoylphorbol 13-acetate-induced apoptosis in vascular smooth muscle cells - Yongna Fan; Ping Xie; Hua Zhang; Shubin Guo; Dongfeng Gu; Mingpeng She; HuiHua Li (Apoptosis, 2022)

Estimating the added value of GRACE total water storage and uncertainty quantification in seasonal streamflow forecasting - Li Liu; Jingkai Xie; Haiting Gu; Yue-Ping Xu (Hydrological Sciences Journal, 2022)

Fiber-optic wireless sensor network using ultra-weak fiber Bragg gratings for vertical subsurface deformation monitoring - Su-Ping Liu; Bin Shi; Kai Gu; Cheng-Cheng Zhang; Jian-Hui He; Jing-Hong Wu; Guang-Qing Wei (Natural Hazards, 2021)

Alpha-Lipoic Acid Attenuates Cadmium- and Lead-Induced Neurotoxicity by Inhibiting Both Endoplasmic-Reticulum Stress and Activation of Fas/FasL and Mitochondrial Apoptotic Pathways in Rat Cerebral Cortex - Yan Yuan; Shi Wen Zhao; Shuang Quan Wen; Qiao Ping Zhu; Li Wang; Hui Zou; Jian Hong Gu; Xue Zhong Liu; Jian Chun Bian; Zong Ping Liu (Neurotoxicity Research, 2021)

LncRNA MYCNOS promotes glioblastoma cell proliferation by regulating miR-216b/FOXM1 axis - Ping Zhao; Ting Li; Youliang Wang; Yong Wang; Qi Gu; Zhi Li (Metabolic Brain Disease, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Interactive effect of water level and flushing rate on population dynamics of a harmful cyanobacterial species: Raphidiopsis raciborskii - Quehui Tang; Lamei Lei; Li Zhao; Jiguang Gu; Lijuan Xiao; Bo-Ping Han (Ecotoxicology, 2021)

Cytotoxic meroterpenoids from the marine sponge Dactylospongia elegans - Hao-Bing Yu; Zi-Fei Yin; Bin-Bin Gu; Jian-Peng Zhang; Shu-Ping Wang; Fan Yang; Hou-Wen Lin (Natural Product Research, 2021)

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

miR-20a Promotes the Axon Regeneration of DRG Neurons by Targeting Nr4a3 - Lili Zhao; Leilei Gong; Ping Li; Jing Qin; Lingchi Xu; Qiyao Wei; Huimin Xie; Susu Mao; Bin Yu; Xiaosong Gu; Songlin Zhou (Neuroscience Bulletin, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

The effects of land use changes on climate warming by source-sink theory - Shuang-shuang Hou; Li-fei Yu; Wei Yan; Shu-hong Gu; Xiao-ping Gu (Arabian Journal of Geosciences, 2021)

Assessing climate change impacts on streamflow and sediment load in the upstream of the Mekong River basin - Di Ma; Budong Qian; Haiting Gu; Zhilin Sun; Yue‐Ping Xu (International Journal of Climatology, 2021)
Assessments of climate change impacts on streamflow and sediment processes are essential for developing science‐based sustainable watershed management plans. We assessed climate change impacts on streamflow and sediment load in the upstream of the Mekong River Basin, as a case study. Future climate scenarios including an ensemble‐mean climate scenario (EnM scenario) were generated based on 20 GCMs in CMIP5, using a stochastic weather generator (LARS‐WG) coupled with a distribution‐free shuffle procedure. The SWAT model was applied to simulate changes in streamflow and sediment load for the future period 2071–2100 under RCP8.5 with respect to the baseline period 1971–2000. Results show that mean monthly maximum and minimum temperature were projected to increase by all the 20 GCMs, with an ensemble‐mean increase of 4.6–5.7°C and 4.2–5.8°C across the 12 months, respectively. An increase in mean annual precipitation (3.4–55.8%) and streamflow (1.0–72.7%) was also projected by all GCMs. However, projected changes in sediment load were not consistent. One half of the GCMs projected an increase (5.2–53.2%) in annual sediment load while the other half projected a decrease (5.1%–43.2%). In each month, at least three‐quarters of the GCMs projected an increase in monthly streamflow. For monthly sediment load, an increase in May to July was projected by over half of the GCMs, while a decrease was projected by a majority of the GCMs for other months. Our results indicate large uncertainties in streamflow and sediment projections under climate change, demonstrating the need to use multi‐model ensembles in climate change impact studies. Moreover, it was found that the streamflow and sediment loads simulated using the EnM scenario were often close to the ensemble means simulated using the 20 GCMs, which implies that the single EnM scenario has the potential of effectively and efficiently estimating the ensemble means of projections in a multi‐model ensemble.

How well do the ERA‐Interim , ERA ‐5, GLDAS ‐2.1 and NCEP‐R2 reanalysis datasets represent daily air temperature over the Tibetan Plateau? - Li Liu; Haiting Gu; Jingkai Xie; Yue‐Ping Xu (International Journal of Climatology, 2021)
Snow and glacier are important components in the hydrological cycle of the Tibetan Plateau (TP). Air temperature, as the main driver in freezing and thawing processes, becomes vital for hydrological modelling and prediction in this region. Due to a sparse ground gauging network, spatial density of air temperature measurement is insufficient for hydro‐meteorological studies. Therefore, the aim of this study is to identify the best representative temperature data for hydrological applications from four widely used reanalysis products, including ERA‐Interim, ERA‐5, GLDAS‐2.1 and NCEP‐R2, with reference to in situ measurements and gridded snow depth from the year 2008–2017 over the entire TP. To reduce errors, Bayesian Joint Probability (BJP) approach based on K‐Nearest Neighbour (KNN) classification algorithm (KNN‐BJP) is proposed to post‐process gridded reanalyses. The results indicate that all the reanalysis datasets provide highly correlated but cold biased air temperature. The correlation ecoefficiency is greater than 0.85. The cold biases are near −3 ° C and mainly distributed in the southeastern TP. Bias in daily maximum temperature during Spring is greater than −8 ° C for most stations. ERA‐Interim is found to have the closest agreement with in situ measurements, closely followed by GLDAS‐2.1. KNN‐BJP is found to be effective within a distance smaller than 5° . After post‐processing, the prominent underestimation is efficiently corrected with Bias near 0. RMSE is markedly reduced to be smaller than 2.5 ° C . The post‐processed ERA‐5 and GLDAS‐2.1 are as accurate as ERA‐Interim, but able to provide more detailed information for extreme events due to their finer spatial resolution. Thus, ERA‐5 and GLDAS‐2.1 are more recommended to represent air temperature in the TP. Snow depth as complementary reference data is able to present spatial variance of air temperature. Our study can help alleviate the problem of sparse air temperature data over the TP.

Stability Analysis of Unsaturated Slopes Considering Combined Influences of Strength Non-homogeneity and Non-saturation - Dan-ping Gu; Tong-hua Ling; Fu Huang; Liang Zhang (Geotechnical and Geological Engineering, 2020)

Land subsidence monitoring in sinking coastal areas using distributed fiber optic sensing: a case study - Su-Ping Liu; Bin Shi; Kai Gu; Cheng-Cheng Zhang; Ji-Long Yang; Song Zhang; Peng Yang (Natural Hazards, 2020)

Combined effects of green manure returning and addition of sewage sludge compost on plant growth and microorganism communities in gold tailings - Yan-Jun Ai; Fu-Ping Li; Hai-Hong Gu; Xiao-Jie Chi; Xue-Tao Yuan; Dong-Yun Han (Environmental Science and Pollution Research, 2020)

Do model parameters change under changing climate and land use in the upstream of the Lancang River Basin, China? - Di Ma; Yue-Ping Xu; Weidong Xuan; Haiting Gu; Zhilin Sun; Zhixu Bai (Hydrological Sciences Journal, 2020)

Species diversity and seasonal dynamics of filamentous cyanobacteria in urban reservoirs for drinking water supply in tropical China - Yang Yang; Xunhao Zheng; Quehui Tang; Jiguang Gu; Lamei Lei; Bo-Ping Han (Ecotoxicology, 2020)

Directed functional connectivity of the hippocampus in patients with presbycusis - Yu-Chen Chen; Wei Yong; Chunhua Xing; Yuan Feng; Nasir Ahmad Haidari; Jin-Jing Xu; Jian-Ping Gu; Xindao Yin; Yuanqing Wu (Brain Imaging and Behavior, 2020)

Predicting postmortem interval based on microbial community sequences and machine learning algorithms - Ruina Liu; Yuexi Gu; Mingwang Shen; Huan Li; Kai Zhang; Qi Wang; Xin Wei; Haohui Zhang; Di Wu; Kai Yu; Wumin Cai; Gongji Wang; et al. (Environmental Microbiology, 2020)
Summary Microbes play an essential role in the decomposition process but were poorly understood in their succession and behaviour. Previous researches have shown that microbes show predictable behaviour that starts at death and changes during the decomposition process. Research of such behaviour enhances the understanding of decomposition and benefits estimating the postmortem interval (PMI) in forensic investigations, which is critical but faces multiple challenges. In this study, we combined microbial community characterization, microbiome sequencing from different organs (i.e. brain, heart and cecum) and machine learning algorithms [random forest (RF), support vector machine (SVM) and artificial neural network (ANN)] to investigate microbial succession pattern during corpse decomposition and estimate PMI in a mouse corpse system. Microbial communities exhibited significant differences between the death point and advanced decay stages. Enterococcus faecalis , Anaerosalibacter bizertensis , Lactobacillus reuteri , and so forth were identified as the most informative species in the decomposition process. Furthermore, the ANN model combined with the postmortem microbial data set from the cecum, which was the best combination among all candidates, yielded a mean absolute error of 1.5 ± 0.8 h within 24‐h decomposition and 14.5 ± 4.4 h within 15‐day decomposition. This integrated model can serve as a reliable and accurate technology in PMI estimation.

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)

A Theoretical Study of Metalloporphyrin-Based Fluorescent Array Sensor using Density Functional Theory - Haiyang Gu; Xingyi Huang; Quansheng Chen; Yanhui Sun; Chin Ping Tan (Journal of Fluorescence, 2020)

DPP-4 Inhibitor Linagliptin is Neuroprotective in Hyperglycemic Mice with Stroke via the AKT/mTOR Pathway and Anti-apoptotic Effects - Gang Zhang; Samuel Kim; Xiaohuan Gu; Shan Ping Yu; Ling Wei (Neuroscience Bulletin, 2020)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

The robustness of the skewness as an early warning signal for abrupt climate change - Xiao‐Qiang Xie; Wen‐Ping He; Bin Gu; Ying Mei; Jinsong Wang (International Journal of Climatology, 2019)
As a dynamical system approaches its critical threshold, the probability density distribution of the system will change significantly. Therefore, it is possible to present an early warning signal based on the changing skewness before reaching the critical threshold. Based on a zero‐dimensional climate model and several typical fold models, this paper systematically studies the influence of noise and missing data on the performance of the skewness coefficient as an early warning signal of an abrupt climate change. The results in three types of fold models show that the skewness coefficient has anti‐noise ability to some extent, but strong noise will significantly reduce the magnitude of the skewness coefficient and the time for early warning will also be shortened. In some cases, strong noise even will lead to the result that the skewness does not work in warning an impending abrupt change. However, the influence of strong noise on skewness is insignificant in the zero‐dimensional climate model. Therefore, the influence of strong noise needs to be considered in the practical application of the skewness coefficient as an early warning signal of an abrupt change. In addition, the results of all the models also indicate that different degrees of the missing data have no statistically significant effect on the warning performance of the skewness coefficient, even when the length of the missing data is up to 20% of the total sample size used in the present paper.

Evaluating the Training of Chinese-Speaking Community Health Workers to Implement a Small-Group Intervention Promoting Mammography - Jiayan Gu; Annette E. Maxwell; Grace X. Ma; Xiaokun Qian; Yin Tan; Hsing-Chuan Hsieh; Shin-Ping Tu; Judy Huei-yu Wang (Journal of Cancer Education, 2019)

Agar extraction from Pyropia haitanensis residue after the removal and purification of phycobiliproteins - Ping Zhao; Jianfeng Niu; Li Huan; Wenhui Gu; Mingjiang Wu; Guangce Wang (Journal of Applied Phycology, 2019)

Can kurtosis be an early warning signal for abrupt climate change? - Xiao-qiang Xie; Wen-ping He; Bin Gu; Ying Mei; Shan-shan Zhao (Climate Dynamics, 2019)

Sediment transport in the Luanhe River delta: grain size trend analysis - Xiaoxiao Yu; Tiegang Li; Dongqi Gu; Aiping Feng; Shihao Liu; Ping Li; Guoqiang Xu; Wenwen Yan; Zhiwei Zhang; Zhengtao Zhu (Journal of Oceanology and Limnology, 2019)

Pyrosequencing of nirS gene revealed spatial variation of denitrifying bacterial assemblages in response to wetland desertification at Tibet plateau - Yun-fu Gu; Ting Liu; Yan Bai; Quan-ju Xiang; Xiao-ping Zhang; Qiang Chen (Journal of Mountain Science, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

A refined model for lithosphere evolution beneath the decratonized northeastern North China Craton - A-Bing Lin; Jian-Ping Zheng; Qing Xiong; Sonja Aulbach; Jiang-Gu Lu; Shao-Kui Pan; Hong-Kun Dai; Hui Zhang (Contributions to Mineralogy and Petrology, 2019)

Concentration of morpholine residues in major fruits and juices and its dietary exposure in China - Pei Cao; Da-Wei Chen; Jiang Liang; Ping-Gu Wu; Sheng Wen; Jing Wei; Si-Jie Liu; Xi-Mei Wu; Yun-Feng Zhao; Hai-Bin Xu (Food Additives & Contaminants: Part A, 2019)

Compressibility of natural schreibersite up to 50 GPa - Xue-Jing He; Jia-Zeng Guo; Xiang Wu; Sheng-Xuan Huang; Fei Qin; Xiang-Ping Gu; Shan Qin (Physics and Chemistry of Minerals, 2019)

Probiotics decrease depressive behaviors induced by constipation via activating the AKT signaling pathway - Nana Xu; Wenting Fan; Xiaoyan Zhou; Yaping Liu; Ping Ma; Suhua Qi; Bing Gu (Metabolic Brain Disease, 2018)

Spatial association between landslides and environmental factors over Guizhou Karst Plateau, China - Xi-liu Yue; Shao-hong Wu; Mei Huang; Jiang-bo Gao; Yun-he Yin; Ai-qing Feng; Xiao-ping Gu (Journal of Mountain Science, 2018)

Segmentation by domestic visitor motivation: Changbai Mountain Biosphere Reserve, China - Xiao-ping Gu; Bernard J. Lewis; Li-jun Niu; Da-pao Yu; Li Zhou; Wang-ming Zhou; Zhen-cai Gong; Zhi-juan Tai; Li-min Dai (Journal of Mountain Science, 2018)

Chemical constituents from Canarium album Raeusch and their anti-influenza A virus activities - Luo-Ping Yang; Xiao-Long Gu; Jin-Xiang Chen; Jie Yang; Sui-Yi Tan; Wen-Jun Duan (Journal of Natural Medicines, 2018)

Recent advances in rapid pathogen detection method based on biosensors - Ying Chen; Zhenzhen Wang; Yingxun Liu; Xin Wang; Ying Li; Ping Ma; Bing Gu; Hongchun Li (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Effects of an additive (hydroxyapatite–biochar–zeolite) on the chemical speciation of Cd and As in paddy soils and their accumulation and translocation in rice plants - Jiao-Feng Gu; Hang Zhou; Wen-Tao Yang; Pei-Qin Peng; Ping Zhang; Min Zeng; Bo-Han Liao (Environmental Science and Pollution Research, 2018)

Mycobacterium tuberculosis Major Facilitator Superfamily Transporters - Ping Li; Yinzhong Gu; Jiang Li; Longxiang Xie; Xue Li; Jianping Xie (The Journal of Membrane Biology, 2017)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Methane enhances aluminum resistance in alfalfa seedlings by reducing aluminum accumulation and reestablishing redox homeostasis - Weiti Cui; Hong Cao; Ping Yao; Jincheng Pan; Quan Gu; Sheng Xu; Ren Wang; Zhaozeng Ouyang; Qingya Wang; Wenbiao Shen (BioMetals, 2017)

Protective effect of dihydropteridine reductase against oxidative stress is abolished with A278C mutation - Yan-ting Gu; Yan-chun Wang; Hao-jun Zhang; Ting-ting Zhao; Si-fan Sun; Hua Wang; Bin Zhu; Ping Li (Journal of Zhejiang University-SCIENCE B, 2017)

Identifying functional groups and ecological roles of tropical and subtropical freshwater Cladocera in Asia - Eric Zeus C. Rizo; Yangliang Gu; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2017)

The biogeographical distribution of tree species-abundance and its relation to climatic factors in mass islands - Xiaoming Li; Chengzhen Wu; Wu Gu; Ran Ye; Haibo Zhang; Ping Qi; Shengqiang Wang; Siying Zhou; Yongjie Wei; Yanhong Cai (Acta Oceanologica Sinica, 2017)

Isolation and characterisation of the epothilone gene cluster with flanks from high alkalotolerant strain Sorangium cellulosum (So0157-2) - Zhi-Feng Li; Li-Ping Zhu; Jing-yan Gu; Raghvendra Pratap Singh; Yue-Zhong Li (World Journal of Microbiology and Biotechnology, 2017)

Spontaneous Remission of Subcutaneous Scedosporiosis Caused by Scedosporium dehoogii in a Psoriatic Patient - Fang-Gu Li; Yan-Ping Yang; Wei Li; Ping Sheng; Wen Li; Wen-Ming Huang; Yi-Ming Fan (Mycopathologia, 2017)

Evaluating historical simulations of CMIP5 GCMs for key climatic variables in Zhejiang Province, China - Weidong Xuan; Chong Ma; Lili Kang; Haiting Gu; Suli Pan; Yue-Ping Xu (Theoretical and Applied Climatology, 2017)

Isoquercetin Ameliorates Cerebral Impairment in Focal Ischemia Through Anti-Oxidative, Anti-Inflammatory, and Anti-Apoptotic Effects in Primary Culture of Rat Hippocampal Neurons and Hippocampal CA1 Region of Rats - Cai-Ping Wang; Yun-Wei Shi; Miao Tang; Xiao-Chuan Zhang; Yun Gu; Xin-Miao Liang; Zhi-Wei Wang; Fei Ding (Molecular Neurobiology, 2017)

Aminopeptidase N5 (APN5) as a Putative Functional Receptor of Cry1Ac Toxin in the Larvae of Athetis lepigone - Li-yu Wang; Shao-hua Gu; Zi-yan Nangong; Ping Song; Qin-ying Wang (Current Microbiology, 2017)

Genetic characterization of H9N2 avian influenza virus in plateau pikas in the Qinghai Lake region of China - Yan Yan; Jin-Yan Gu; Zhuang-Chuan Yuan; Xin-Yu Chen; Zeng-Kui Li; Jing Lei; Bo-li Hu; Li-Ping Yan; Gang Xing; Min Liao; Ji-Yong Zhou (Archives of Virology, 2017)

Substrate color preference and feeding by juvenile Chinese sturgeon Acipenser sinensis: exploration of a behavioral adaptation - Xiaolian Gu; Ping Zhuang; Feng Zhao; Xiaotao Shi; Xiaorong Huang; Guangpeng Feng; Tao Zhang; Jianyi Liu; Longzhen Zhang; Boyd Kynard (Environmental Biology of Fishes, 2017)

A novel method for detecting abrupt dynamic change based on the changing Hurst exponent of spatial images - Wen-Ping He; Qun-Qun Liu; Bin Gu; Shan-Shan Zhao (Climate Dynamics, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

Comparative genomic analysis of Lactobacillus plantarum ZJ316 reveals its genetic adaptation and potential probiotic profiles - Ping Li; Xuan Li; Qing Gu; Xiu-yu Lou; Xiao-mei Zhang; Da-feng Song; Chen Zhang (Journal of Zhejiang University-SCIENCE B, 2016)

Effect of Stress from Cadmium Combined with Different Levels of Molybdenum on Serum Free Radical and Expression of Related Apoptosis Genes in Goat Livers - Huabin Cao; Chenghong Xing; Yu Zhuang; Xiaolong Gu; Junrong Luo; Xiaoquan Guo; Ping Liu; Caiying Zhang; Guoliang Hu (Biological Trace Element Research, 2016)

Genome-wide identification and characterization of the Dof gene family in moso bamboo (Phyllostachys heterocycla var. pubescens) - Tao Wang; Jin-Jun Yue; Xue-Ji Wang; Lu Xu; Lu-Bin Li; Xiao-Ping Gu (Genes & Genomics, 2016)

Empirical calibration of the clinopyroxene–garnet magnesium isotope geothermometer and implications - Wang-Ye Li; Fang-Zhen Teng; Yilin Xiao; Hai-Ou Gu; Xiang-Ping Zha; Jian Huang (Contributions to Mineralogy and Petrology, 2016)

Expression of the NMDA receptor subunit GluN3A (NR3A) in the olfactory system and its regulatory role on olfaction in the adult mouse - Jin Hwan Lee; Ling Wei; Todd C. Deveau; Xiaohuan Gu; Shan Ping Yu (Brain Structure and Function, 2016)

Varying Dietary Levels of Molybdenum Inducing Cell Apoptosis of Spleen Under Cadmium Stress in Caprine - Qingyang Xiao; Caiying Zhang; Xiaolong Gu; Yu Zhuang; Junrong Luo; Ping Liu; Xiaoquan Guo; Guoliang Hu; Huabin Cao (Biological Trace Element Research, 2016)

Suppression of nighttime sap flux with lower stem photosynthesis in Eucalyptus trees - Jianguo Gao; Juan Zhou; Zhenwei Sun; Junfeng Niu; Cuiming Zhou; Daxing Gu; Yuqing Huang; Ping Zhao (International Journal of Biometeorology, 2016)

Risk Assessment for Ecological Planning of Arid Inland River Basins Under Hydrological and Management Uncertainties - Jinjin Gu; Mo Li; Ping Guo; Guohe Huang (Water Resources Management, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Anthropogenic activities drive the microbial community and its function in urban river sediment - Xu Zhang; Qing Gu; Xi-En Long; Zhao-Lei Li; Dong-Xiu Liu; Dan-Hua Ye; Chi-Quan He; Xiao-Yan Liu; Kristiina Väänänen; Xue-Ping Chen (Journal of Soils and Sediments, 2016)

Body mass index and weight change in relation to triple-negative breast cancer survival - Ping-Ping Bao; Hui Cai; Peng Peng; Kai Gu; Yinghao Su; Xiao-Ou Shu; Ying Zheng (Cancer Causes & Control, 2016)

Travel motivation of domestic tourists to the Changbai Mountain Biosphere Reserve in Northeastern China: A comparative study - Xiao-ping Gu; Bernard J. Lewis; Yan-quan Li; Da-pao Yu; Li Zhou; Wang-ming Zhou; Sheng-nan Wu; Li-min Dai (Journal of Mountain Science, 2015)

Molecular cloning of class III chitinase gene from Avicennia marina and its expression analysis in response to cadmium and lead stress - Li-Ying Wang; You-Shao Wang; Jing-Ping Zhang; Ji-Dong Gu (Ecotoxicology, 2015)

Genetic population structure of polychaeta Neanthes glandicincta (Nereididae) of the Mai Po Inner Deep Bay Ramsar Site, Hong Kong - Ping-Ping Shen; Ji-Dong Gu (Ecotoxicology, 2015)

Generation and characterization of Brassica rapa ssp. pekinensis – B. oleracea var. capitata monosomic and disomic alien addition lines - AI XIA GU; SHU XING SHEN; YAN HUA WANG; JIAN JUN ZHAO; SHU XIN XUAN; XUE PING CHEN; XIAO FENG LI; SHUANG XIA LUO; YU JING ZHAO (Journal of Genetics, 2015)

Autophagy protects meniscal cells from glucocorticoids-induced apoptosis via inositol trisphosphate receptor signaling - Chao Shen; Wen Gu; Gui-Quan Cai; Jian-Ping Peng; Xiao-Dong Chen (Apoptosis, 2015)

Dynamic evolution of resistance gene analogs in the orthologous genomic regions of powdery mildew resistance gene MlIW170 in Triticum dicoccoides and Aegilops tauschii - Yong Liang; De-Yun Zhang; Shuhong Ouyang; Jingzhong Xie; Qiuhong Wu; Zhenzhong Wang; Yu Cui; Ping Lu; Dong Zhang; Zi-Ji Liu; Jie Zhu; Yong-Xing Chen; et al. (Theoretical and Applied Genetics, 2015)

Contribution of mitochondrial function to exercise-induced attenuation of renal dysfunction in spontaneously hypertensive rats - Qi Gu; Li Zhao; Yan-Ping Ma; Jian-Dong Liu (Molecular and Cellular Biochemistry, 2015)

Bioactive Substances from Marine Fishes, Shrimps, and Algae and Their Functions: Present and Future - Ping Yu; Huifen Gu (Critical Reviews in Food Science and Nutrition, 2015)

Comparison of non-volatile taste-active compounds between the cooked meats of pre- and post-spawning Yangtze Coilia ectenes - Jin-yuan Zheng; Ning-ping Tao; Jun Gong; Sai-Qi Gu; Chang-hua Xu (Fisheries Science, 2015)

Immunosuppressive Effect of Hypodermin C on Complement Component 3 In Vitro - An-Kang Hu; Ren-Jin Chen; Xiao-Rong Zhu; Jian-Hong Gu; Zong-Ping Liu (Cell Biochemistry and Biophysics, 2015)

Two new triterpenoid saponins obtained by microbial hydrolysis with Alternaria alternata AS 3.6872 - Li-Hua Mu; Yong-Jie Gu; Bai-Ping Ma; Li Lu; Ping Liu (Natural Product Research, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Soy isoflavone intake and bone mineral density in breast cancer survivors - Michelle L. Baglia; Kai Gu; Xianglan Zhang; Ying Zheng; Peng Peng; Hui Cai; Ping-Ping Bao; Wei Zheng; Wei Lu; Xiao-Ou Shu (Cancer Causes & Control, 2015)

Erratum to: Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Effects of hydraulic retention time and nitrobenzene concentration on the performance of sequential upflow anaerobic filter and air lift reactors in treating nitrobenzene-containing wastewater - Jinhua Wu; Guocai Chen; Jingjing Gu; Weizhao Yin; Mengxiong Lu; Ping Li; Bo Yang (Environmental Science and Pollution Research, 2014)

Multi-time scale analysis of runoff at the Yangtze estuary based on the Morlet Wavelet Transform method - Cui-ping Kuang; Ping Su; Jie Gu; Wu-jun Chen; Jian-le Zhang; Wan-lei Zhang; Yong-feng Zhang (Journal of Mountain Science, 2014)

Bio-beads with immobilized anaerobic bacteria, zero-valent iron, and active carbon for the removal of trichloroethane from groundwater - Ya-Zhen Zhou; Jie Yang; Xiao-Li Wang; Yue-Qing Pan; Hui Li; Dong Zhou; Yong-Di Liu; Ping Wang; Ji-Dong Gu; Qiang Lu; Yue-Feng Qiu; Kuang-Fei Lin (Environmental Science and Pollution Research, 2014)

Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Influence of casein phosphopeptide-amorphous calcium phosphate application, smear layer removal, and storage time on resin-dentin bonding - Jun Lin; Wei-ying Zheng; Peng-ruo-feng Liu; Ning Zhang; Hui-ping Lin; Yi-jing Fan; Xin-hua Gu; Oliver Vollrath; Christian Mehl (Journal of Zhejiang University-SCIENCE B, 2014)

Aquamicrobium terrae sp. nov., isolated from the polluted soil near a chemical factory - Zhi-Guo Wu; Fang Wang; Cheng-Gang Gu; Yin-Ping Zhang; Zong-Zheng Yang; Xiao-Wei Wu; Xin Jiang (Antonie van Leeuwenhoek, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Estrogen receptor α gene PvuII polymorphism and coronary artery disease: a meta-analysis of 21 studies - Jie Ding; Hui Xu; Xiang Yin; Fu-rong Zhang; Xiao-ping Pan; Yi-an Gu; Jun-zhu Chen; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2014)

Sex identification and genetic variation of Saccharina (Phaeophyta) gametophytes as revealed by inter-simple sequence repeat (ISSR) markers - Jun-Gang Gu; Yu-Ping Sun; Yu Liu; Yan-Hui Bi; Zhi-Gang Zhou (Journal of Applied Phycology, 2014)

Assessment of wheat variety stability using SSR markers - Li Xin Wang; Hong Bo Li; Tie Cheng Gu; Li Hua Liu; Bin Shuang Pang; Jun Qiu; Chang Ping Zhao (Euphytica, 2014)

Efficacy of Nimotuzumab Combined with Docetaxel–Cisplatin–Fluorouracil Regimen in Treatment of Advanced Oral Carcinoma - Jian Meng; Qian-ping Gu; Qing-fei Meng; Jie Zhang; Zhi-ping Li; Ya-meng Si; Wei Guo; Qian-wei Zhuang (Cell Biochemistry and Biophysics, 2014)

Radioactive Seed Implantation Combined with Prosthesis Denture in Treatment of Oral and Maxillofacial Malignancy - Jian Meng; Qing-fei Meng; Qian-ping Gu; Ya-meng Si; Hao Zheng; Jie Zhang; Zhi-ping Li; Qian-wei Zhuang (Cell Biochemistry and Biophysics, 2013)

Characterization and expression of gamma-interferon-inducible lysosomal thiol reductase (GILT) gene in rainbow trout (Oncorhynchus mykiss) with implications for GILT in innate immune response - Meng Liu; Hongyan Liu; Xiaocui Guan; Hongxin Ai; Haitao Wu; Ping Liu; Wei Gu; Shuangquan Zhang (Immunogenetics, 2013)

The discovery of 3-(1-aminoethylidene)quinoline-2, 4(1H,3H)-dione derivatives as novel PSII electron transport inhibitors - Yu-Xiu Liu; Hua-Ping Zhao; Zi-Wen Wang; Yong-Hong Li; Hai-Bin Song; Hannah Riches; David Beattie; Yu-Cheng Gu; Qing-Min Wang (Molecular Diversity, 2013)

Exercise after diagnosis and metabolic syndrome among breast cancer survivors: a report from the Shanghai Breast Cancer Survival Study - Ping-Ping Bao; Ying Zheng; Sarah Nechuta; Kai Gu; Hui Cai; Peng Peng; Xiao-Ou Shu; Wei Lu (Cancer Causes & Control, 2013)

Identification and expression profile analysis of odorant-binding protein genes in Apolygus lucorum (Hemiptera: Miridae) - Ping Ji; Shao-Hua Gu; Jing-Tao Liu; Xiao-Qiang Zhu; Yu-Yuan Guo; Jing-Jiang Zhou; Yong-Jun Zhang (Applied Entomology and Zoology, 2013)

Perifosine Induces Cell Apoptosis in Human Osteosarcoma Cells: New Implication for Osteosarcoma Therapy? - Chen Yao; Jian-jun Wei; Zu-yu Wang; Hui-min ding; Dong Li; Shi-chang Yan; Yong-jiang Yang; Zhang-ping Gu (Cell Biochemistry and Biophysics, 2013)

The relationship between carbon and nitrogen stable isotopes of zooplankton and select environmental variables in low-latitude reservoirs - Wei Hou; Binhe Gu; Huajun Zhang; Jiguang Gu; Bo-Ping Han (Limnology, 2013)

Formaldehyde Impairs Learning and Memory Involving the Disturbance of Hydrogen Sulfide Generation in the Hippocampus of Rats - Xiao-Qing Tang; Yuan-Yuan Zhuang; Ping Zhang; Heng-Rong Fang; Cheng-Fang Zhou; Hong-Feng Gu; Hui Zhang; Chun-Yan Wang (Journal of Molecular Neuroscience, 2013)

Contribution of hydrogen sulfide and nitric oxide to exercise-induced attenuation of aortic remodeling and improvement of endothelial function in spontaneously hypertensive rats - Qi Gu; Bing Wang; Xiao-Feng Zhang; Yan-Ping Ma; Jian-Dong Liu; Xiao-Ze Wang (Molecular and Cellular Biochemistry, 2012)

Resveratrol Attenuates Doxorubicin-Induced Cardiomyocyte Apoptosis in Lymphoma Nude Mice by Heme Oxygenase-1 Induction - Jun Gu; Zhi-ping Song; Dong-mei Gui; Wei Hu; Yue-guang Chen; Da-dong Zhang (Cardiovascular Toxicology, 2012)

Determination of methylmercury in marine fish from coastal areas of Zhejiang, China - Zhu Huang; Xiao-Dong Pan; Jian-Long Han; Ping-Gu Wu; Jun Tang; Ying Tan (Food Additives & Contaminants Part B-Surveillance, 2012)

Evaluation of sampling sizes on the intertidal macroinfauna assessment in a subtropical mudflat of Hong Kong - Ping-Ping Shen; Hong Zhou; Zhenye Zhao; Xiao-Zhang Yu; Ji-Dong Gu (Ecotoxicology, 2012)

Novel polymorphism of internal transcribed spacers (ITS) and their utilization in phylogenetic analysis of Neanthes glandicincta (Annelida: Polychaeta: Nereididae) - Ping-Ping Shen; Hong Zhou; Ji-Guang Gu (Ecotoxicology, 2012)

Analyses of n-alkanes degrading community dynamics of a high-temperature methanogenic consortium enriched from production water of a petroleum reservoir by a combination of molecular techniques - Lei Zhou; Kai-Ping Li; Serge Maurice Mbadinga; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Ecotoxicology, 2012)

Evidence of iron cyanides as supplementary nitrogen source to rice seedlings - Xiao-Zhang Yu; Ping-Ping Shen; Ji-Guang Gu; Yan Zhou; Fu-Zhong Zhang (Ecotoxicology, 2012)

Survivals of D. galeata in sub-tropical reservoirs: harmful effects of toxic cyanobacteria in food source - Bo-Ping Han; Xian Lin; Lamei Lei; Jiguang Gu (Ecotoxicology, 2012)

Construction of Escherichia coli strains producing l-serine from glucose - Yu Li; Gu-Kui Chen; Xin-Wei Tong; Hui-Tu Zhang; Xiao-Guang Liu; Yi-Han Liu; Fu-Ping Lu (Biotechnology Letters, 2012)

Identification of volatile components in yak butter using SAFE, SDE and HS-SPME-GC/MS - Ning Li; Bao-Guo Sun; Fu-Ping Zheng; Hai-Tao Chen; Si-Yuan Liu; Chen Gu; Zhen-Yang Song (Natural Product Research, 2012)

The estimate of sea ice resources quantity in the Bohai Sea based on NOAA/AVHRR data - Shuai Yuan; Wei Gu; Yingjun Xu; Ping Wang; Shuqing Huang; Zhangyan Le; Jianou Cong (Acta Oceanologica Sinica, 2012)

Polyethylenimine-cyclodextrin-tegafur conjugate shows anti-cancer activity and a potential for gene delivery - Qi-da Hu; Hui Fan; Wei-jian Lou; Qing-qing Wang; Gu-ping Tang (Journal of Zhejiang University-SCIENCE B, 2011)

Prediction of conserved microRNAs from skin and mucosal human papillomaviruses - Wenyi Gu; Jiyuan An; Ping Ye; Kong-Nan Zhao; Annika Antonsson (Archives of Virology, 2011)

Mimecan is involved in aortic hypertrophy induced by sinoaortic denervation in rats - Xiao-Song Gu; Jun-Ping Lei; Jian-Bo Shi; Wen-ling Lian; Xiang Yang; Xing Zheng; Yong-Wen Qin (Molecular and Cellular Biochemistry, 2011)

Requirement of regulated endocrine-specific protein-18 for development and expression of regulated endocrine-specific protein-18 isoform c in mice - Min Liang; Jian Ling Yang; Min Juan Bian; Jie Liu; Xiao Qi Hong; Yan Cong Wang; Yu Fang Huang; Shu Ping Gu; Mei Yu; Fang Huang; Jian Fei (Molecular Biology Reports, 2011)

Genotype-phenotype correlations in Chinese patients with TGFBI gene-linked corneal dystrophy - Yan Long; Yang-shun Gu; Wei Han; Xiu-yi Li; Ping Yu; Ming Qi (Journal of Zhejiang University-SCIENCE B, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Remote chlorophyll- a retrieval in Case-II waters using an improved model and IRS-P6 satellite data - Jing-Ping Xu; Fang Li; Bai Zhang; Xing-Fa Gu; Tao Yu (International Journal of Remote Sensing, 2010)

Effects of Cadmium on Absorption, Excretion, and Distribution of Nickel in Rats - Zhan Li; Jun-Ying Gu; Xian-Wen Wang; Qiao-Hui Fan; Yan-Xia Geng; Zong-Xian Jiao; Yi-Ping Hou; Wang-Suo Wu (Biological Trace Element Research, 2010)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Prediction of shelled shrimp weight by machine vision - Peng-min Pan; Jian-ping Li; Gu-lai Lv; Hui Yang; Song-ming Zhu; Jian-zhong Lou (Journal of Zhejiang University-SCIENCE B, 2009)

Necessity of Screening Water Chestnuts for Microcystins After Cyanobacterial Blooms Break Out - Fu-Gang Xiao; Xiao-Lian Zhao; Jian Tang; Xiao-Hong Gu; Jing-Ping Zhang; Wei-Min Niu (Archives of Environmental Contamination and Toxicology, 2009)

Pb/Cu effects on the organization of microtubule cytoskeleton in interphase and mitotic cells of Allium sativum L. - Donghua Liu; Ping Xue; Qingmin Meng; Jing Zou; Jiegang Gu; Wusheng Jiang (Plant Cell Reports, 2009)

Determination of Microcystin-LR in Water from Lake Tai, China - Fu-Gang Xiao; Xiao-Lian Zhao; Jian Tang; Xiao-Hong Gu; Jing-Ping Zhang; Wei-Min Niu (Bulletin of Environmental Contamination and Toxicology, 2009)

An improved design of PCR primers for detection of human T cell receptor β chain repertoire - Yuan Ou; Chunrong Tong; Ying Zhang; Peng Cai; Jiangying Gu; Yan Liu; Hongxing Liu; He Wang; Bin Chu; Ping Zhu (Molecular Biology Reports, 2009)

Evaled Expression of ICAM-1 and Its Ligands in the Rat Spinal Cord Following Lipopolysaccharide Intraspinal Injection - Junling Yang; Min Fei; Yangyang Gu; Linlin Sun; Zhiyun Ben; Dan Zhou; Jianping Chen; Youhua Wang; Ping Wang; Aiguo Shen; Chun Cheng (NeuroMolecular Medicine, 2008)

Proteasome-dependent inactivation of Akt is essential for 12-O-tetradecanoylphorbol 13-acetate-induced apoptosis in vascular smooth muscle cells - Yongna Fan; Ping Xie; Hua Zhang; Shubin Guo; Dongfeng Gu; Mingpeng She; HuiHua Li (Apoptosis, 2008)

Polychlorinated Biphenyls (PCBs) in PM10 Surrounding a Chemical Industrial Zone in Shanghai, China - Jin-Ping Cheng; Qian Wu; Hai-Ying Xie; Jin-Min Gu; Wen-Chang Zhao; Jing Ma; Wen-Hua Wang (Bulletin of Environmental Contamination and Toxicology, 2007)

Receptor-mediated gene delivery using polyethylenimine (PEI) coupled with polypeptides targeting FGF receptors on cells surface - Da Li; Qing-qing Wang; Gu-ping Tang; Hong-liang Huang; Fen-ping Shen; Jing-zhong Li; Hai Yu (Journal of Zhejiang University-SCIENCE B, 2006)

High RAPD but no cpDNA sequence variation in the endemic and endangered plant, Heptacodium miconioides Rehd. (Caprifoliaceae) - Hui-Ping Lu; Yue-Wei Cai; Xiao-Yong Chen; Xin Zhang; Yong-Jie Gu; Guang-Fu Zhang (Genetica, 2006)

A Study of the Adaptive Method for Decoupling Overlapping Seismic Records - Xuanhui Yang; Yu Jeffrey Gu; Ping Shen; Xiqiang Liu; Zhizhen Zheng (Pure and Applied Geophysics, 2006)

Degradability of dimethyl terephthalate by Variovorax paradoxus T4 and Sphingomonas yanoikuyae DOS01 isolated from deep-ocean sediments - Yu Ping Wang; Ji-Dong Gu (Ecotoxicology, 2006)

A clinical and molecular-genetic analysis of Chinese patients with lattice corneal dystrophy and novel Thr538Pro mutation in theTGFBI (BIGH3) gene - Ping Yu; Yangshun Gu; Yuehong Yang; Xiaoyi Yan; Liu Chen; Zhen Ge; Ming Qi; Jianmin Si; Lei Guo (Journal of Genetics, 2006)

Isolation and structure revision of 10-deacetyltaxinine from the seeds of the Chinese yew, Taxus mairei - Qing-Wen Shi; Zuo-Ping Li; Ding Zhao; Ji-Shun Gu; Hiromasa Kiyota (Natural Product Research, 2006)

Identification of a New Transcript Specifically Expressed in Mouse Spermatocytes: mmrp2 - Shanye Gu; Jiarui Hu; Ping Song; Wuming Gong; Ming Guo (Molecular Biology Reports, 2005)

Karyomorphology of Maianthemum sensu lato (Polygonatae, Ruscaceae) - Ying Meng; Ze-Long Nie; Yong-Ping Yang; Zhi-Jian Gu (Journal of Plant Research, 2005)

Protoplast culture and paclitaxel production by Taxus yunnanensis - Jian-Ping Luo; Qing Mu; Yue-Hua Gu (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Srbl maps to mouse Chromosome 5 in a region harboring putative QTLs for plasma lipoprotein levels - Carrie L. Welch; Yu-Rong Xia; Ling-Jie Gu; Dietrich Machleder; Margarete Mehrabian; Ping-Zi Wen; Nancy Webb; Willem J. S. de Villiers; Deneys van der Westhuyzen; Aidons J. Lusis (Mammalian Genome, 1997)